2013
DOI: 10.1371/journal.pone.0061403
|View full text |Cite
|
Sign up to set email alerts
|

PIN2 Turnover in Arabidopsis Root Epidermal Cells Explored by the Photoconvertible Protein Dendra2

Abstract: The steady state level of integral membrane proteins is dependent on a strictly controlled delivery and removal. Here we show that Dendra2, a green-to-red photoconvertible fluorescent protein, is a suitable tool to study protein turnover in plants. We characterized the fluorescence properties of Dendra2 expressed either as a free protein or as a tag in Arabidopsis thaliana roots and optimized photoconversion settings to study protein turnover. Dendra2 was fused to the PIN2 protein, an auxin transporter in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
46
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 60 publications
2
46
1
Order By: Relevance
“…The finding that 1-NAA is not able to inhibit endocytosis of PIN2, was confirmed in a modified photoconversion experiment. In this case, we firstly photoconverted PIN2-Dendra2 in roots and after that, we kept seedlings under standard cultivation conditions for 2 h. As expected in the context of our previous studies (Jásik et al, 2013;Jásik and Schmelzer, 2014), after 2 h, a significant part of the PM PIN2 population was already replaced by the newly synthesized green fluorescing form (Fig. 3).…”
mentioning
confidence: 73%
See 4 more Smart Citations
“…The finding that 1-NAA is not able to inhibit endocytosis of PIN2, was confirmed in a modified photoconversion experiment. In this case, we firstly photoconverted PIN2-Dendra2 in roots and after that, we kept seedlings under standard cultivation conditions for 2 h. As expected in the context of our previous studies (Jásik et al, 2013;Jásik and Schmelzer, 2014), after 2 h, a significant part of the PM PIN2 population was already replaced by the newly synthesized green fluorescing form (Fig. 3).…”
mentioning
confidence: 73%
“…The abovementioned discrepancies prompted us to perform a more complex study on the influence of different auxins and auxin transport inhibitors on PIN2 intracellular dynamics using the photoconvertible fluorescence protein method. In our earlier study (Jásik et al, 2013), we demonstrated that Dendra2 as a tag is not photoconverted under standard confocal imaging conditions using the 488 nm line of the Argon laser for excitation. Therefore, Dendra2 can be used as a classical fluorescence protein tag similar to GFP.…”
mentioning
confidence: 85%
See 3 more Smart Citations